Response to recurrent selection for stover feeding value in pearl millet variety ICMV 221 - Bidinger, F.R.; Blümmel, Michael; Hash, C.T. (2006)
The objectives of the present work were threefold: first, to determine the ranges of grain and stover yields and stover quality traits in full-sib progenies of pearl millet cultivar ICMV 221; second, to assess changes in grain and stover characteristics in trait-specific experimental varieties generated by random-mating selected subsets of these full-sib progenies; and third, to compare laboratory estimates of stover quality traits used for selection among progenies in the full-sib population with direct measurements of stover quality traits obtained through animal feeding trials, using stover samples from replicated field trials of the experimental varieties.